Intersectorality. Multiplicative discrimination effects. Gender/Sex, citizenship and Freedom of choice. - López-Narbona, Ana María; Ortega-Gaspar, María Marta (My University, 2022)
Intersectionality is the process of discrimination and oppression that individuals and groups experience in a complex, dynamic, multidimensional, and unique way. Social structures contribute to consolidate and perpetuate intersectionality. Using data from the World Values Survey (Waves 6th, 2010-2014, and 7th, 2017, 2020), this work proposes the analysis of intersectionality experienced by women in comparison to men, in countries such as the United States, Japan, Spain, United Kingdom, France, Sweden and Germany. WVS offers a wide range of variables to analyze the attitudes and behaviors of interviewees on a variety of topics, in which women and men actively participate, such as labor market, personal relationships, individual rights, cultural aspects such as values, ideals and beliefs. Attitudes and behaviors are strong predictors of the nature and form of social structures as the basis of inequalities, discriminations and oppressions. First, the objective of this work is to determine theoretically which are the main dimensions of a social structure which support and perpetuate intersectionality. Secondly, we will apply Principal Component Analysis (PCA) to WVS data in order to reduce the dimensionality of this dataset to increase interpretability minimizing information and identifying the dimensions which explain gender intersectionality in the proposed countries and years.
Keywords: Sociología - Investigación; Discriminación sexual; Intersectorality; Multiplicative discrimination; Gender/sex; Citizenship; Freedom of choice; Comparative sociology